Trends and Impacts of Different Barriers on Bangladeshi RMG Industry’s Sustainable Development - Hasan, Md. Morshadul; Parven, Tanjina; Khan, Shajib; Mahmud, Appel; Yajuan, Lu (Universitas Prasetiya Mulya, 2018)
The main objective of this research is to investigate the trends and impacts of different barriers to Bangladeshi Ready-Made Garments (RMG) industry’s growth and sustainable development. The influencing factors or barriers have identified and their impacts have explored in this research. The trends of identified factors have shown with their specific reasons. Data of this research have collected from the apparel industry located in Dhaka (North & South) and Gazipur City Corporation area using different techniques based on random sampling from its fixed population specified by Bangladesh Garment Manufacturers and Exporters Association (BGMEA). It has been found that most of the factors have a decreasing trend with mostly moderate impacts on the RMG industry’s growth and development. The most important reason for this research is to help the investors who are going to invest in Bangladeshi apparel sector by showing the present scenario.